Oncolytic Sendai Virus Therapy of Canine Mast Cell Tumors (A Pilot Study) - Ilyinskaya, Galina V.; Mukhina, Elena V.; Soboleva, Alesya V.; Matveeva, Olga V.; Chumakov, Peter M. (Frontiers in Veterinary Science, 2018)
Abstract BACKGROUND: Canine mastocytomas (mast cell tumors) represent a common malignancy among many dog breeds. A typical treatment strategy for canine mastocytomas includes surgery, chemo- and radiotherapy, although in many cases the therapy fails and the disease progression resumes. New treatment approaches are needed. AIMS: The goal of this pilot study was to examine safety and efficacy of oncolytic Sendai virus therapy administered to canine patients with cutaneous or subcutaneous mastocytomas. MATERIALS AND METHODS: Six canine patients, with variable grades and stages of the disease, received virus therapy, either as a monotherapy, or in combination with surgery. The therapy included two or more virus applications administered weekly or biweekly. Each application of Sendai virus (107 to 108.6 EID50) consisted of multiple individual 0.01-0.1ml injections delivered intratumorally, intradermally around a tumor, and under a tumor bed. RESULTS: The treatment was well tolerated, with minor transitory side effects. Of the six dogs, two did not receive surgery or any other treatment besides the virus injections. The other four animals underwent radical or debulking surgeries, and in three of them the subsequent administration of Sendai virus completely cleared locally recurrent or/and remaining tumor masses. Five dogs demonstrated a complete response to the treatment, the animals remained disease free during the time of observation (2-3 years). One dog responded only partially to the virotherapy; its after-surgical recurrent tumor and some, but not all, metastases were cleared. This dog had the most advanced stage of the disease with multiple enlarged lymph nodes and cutaneous metastases. CONCLUSION: The results of the pilot study suggest that Sendai virus injections could be safe and efficient for the treatment of dogs affected by mastocytomas. They also suggest the need of further studies for finding optimal schemes and schedules for this kind of therapy.